Valuasi Ekonomi Kelayakan Pembangunan Hotel Sutan Raja Di Kota Kendari - Erma Widiani; Rosalina Kumalawati (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study aims to improve the economic and financial feasibility of the Sutan Raja Hotel development  in Kendari City. This four-star hotel is planned to be built in a strategic location, specifically on Jalan  Supu Yusuf, Korumba Village, Mandonga District. The analysis was conducted using three main  indicators, namely Net Present Value (NPV), Benefit Cost Ratio (BCR), and Internal Rate of Return  (IRR). The calculation results show that the project generates an NPV of IDR 88.05 billion, a BCR of  1.33, and an IRR of 13.54%. Based on these results, the project is considered economically and financially feasible. The strategic location factor and tourism potential in Kendari City are the main supporters of the success of this investment.